Outsourcing of port operator business processes: the case of state enterprise “commercial sea port “chornomorsk”” - Shcherbyna, Veronika; Navrozova, Yuliya; Matviienko, Maryna (International Journal of Engineering and Technology, 2026)
In modern conditions, port operators are forced not only to maintain a constant competitor in the struggle for freight traffic, but to implement structural transformations, to update management methods, to change the specifics of relationships with business partners. One of these methods is outsourcing. It allows to reduce port operator costs and to focus on the main types of activities. The categories of port operator business processes are clustered in the article depending on the possibility of transfer to outsourcing. Business processes to be outsourced to reduce costs are considered. The possibility of outsourcing port operator business processes based on outsourcing complex effect calculation is substantiated. To confirm the results presented in the article, the calculations were made for state port operator and its department.